ANCHORS: A multi‐decadal tide gauge dataset to monitor Australian relative sea level changes. (24th November 2021) - Hague, Ben S.; Jones, David A.; Trewin, Blair; Jakob, Doerte; Murphy, Bradley F.; Martin, David J.; Braganza, Karl
Abstract: Here, we describe a new national tide gauge‐based sea level dataset for monitoring sea level changes around Australia, and the novel homogenization methodology used to develop it. Homogenization is a two‐step process that involves the detection of jumps or steps in the data (inhomogeneities) followed by a correction applied to remove the change. This new dataset is called the Australian National Collection of Homogenized Observations of Relative Sea Level (ANCHORS). ANCHORS provides coastal sea levels at hourly resolution with homogenization performed on annual means. ANCHORS is intended to be a national tide gauge‐based sea level dataset to monitor changes in mean sea level and resultant coastal flood frequency changes around Australia. Whilst sea levels are rising around Australia in response to global mean sea level changes, coastal water levels represent a notable gap in the suite of in situ high‐quality datasets available for researchers, governments and industry. Tide gauge datasets are well suited to impact‐based assessments of changes in flood frequency, duration and risk. In this regard, ANCHORS will sit alongside existing satellite‐ and numerical modelling‐based sea level datasets to provide enhanced insights into the physical impacts of sea level rise on Australian coastlines. We have adapted established homogenization techniques to develop a national collection of homogenous long tide gauge records. The dataset comprises 38 tide gauge records from around Australia, varying in length from 34 to 123 years, with an average of 57 years. Finally, we discuss limitations and potential applications for ANCHORS and how these have informed the design of this coastal sea level dataset. Abstract : The Australian National Collection of Homogenised Observations of Relative Sea Level (ANCHORS) is a dataset of hourly relative sea levels. The dataset comprises 38 tide gauge records from around Australia, varying in length from 34 to 123 years, with an average of 57 years. We have developed, and subsequently applied, methods to remove the effects of non‐geophysical changes in the data (a process called homogenization), allowing a consistent definition of annual relative mean sea level throughout the ANCHORS records.